Vertical Juvenile School: Space Planning - Lu, Min Yun; Basher, Hazril Sherney (MAJ - Malaysia Architectural Journal, 2020)
The universe’s criminal justice system is very broad and contains many forms of facilities. By the rights of children, every child deserves equality and dignity. Therefore, in detention centers, children must be separated from all adults in every care, to ensure their protection and right to better recovery. According to the United Nation, the increase in population will increase the number of criminal issues. In addition to juvenile delinquency, the number of criminal cases is estimated to be higher than reported. The United Nations has therefore taken these issues seriously and has adopted all the recommendations on childcare and treatment. Thus, this research aims to identify vertical juvenile school space planning to encounter the issues of increasing juvenile criminal crime in the future. This research is recommended to assist the government agencies, academics, policy-makers, and architects and researchers towards constructing vertical juvenile schools under international and local recognized practices for children committing offenses.